Superconducting nanowire single-photon detector made of ultrathin γ-Nb4N3 film for mid-infrared wavelengths. (17th May 2021) - Pan, Yiming; Zhou, Hui; Zhang, Lu; Li, Hao; Tang, Yan; Yu, Huiqin; Si, Mengting; You, Lixing; Wang, Zhen
Abstract: Superconducting nanowire single-photon detectors (SNSPDs) made of ultrathin δ -NbN films have been widely applied in both visible and infrared wavelengths. For mid-infrared (MIR) wavelengths, SNSPDs made of tungsten silicide films with a lower critical temperature were reported up to 9.9 μ m wavelength. In this study, we demonstrate the potential of NbN-SNSPDs for use in MIR applications. SNSPDs made of γ -Nb4 N3 films (critical temperature of 5.1 K for 6.5 nm thick films) instead of δ -NbN films were fabricated. The dependence of the normalized detection efficiency on the bias current indicated a clear trend toward a saturated plateau for wavelengths up to 2145 nm. The calculated cut-off wavelengths indicated the possibility of using γ -Nb4 N3 SNSPDs for longer MIR wavelengths.